L'An prochain à Jerusalem - Chtcharansky, Avital; Ban-Josef, Ilana; Albeck, Raymond; Duarc, Robert Fouques ([S.l]: Stock, 1979)
"Originale titel : Next year in Jerusalem / Morrow, William .- New York, 1979"